2021
DOI: 10.1177/11786221211013332
|View full text |Cite
|
Sign up to set email alerts
|

Testing Possible Scenario-Based Responses of Vegetation Under Expected Climatic Changes in Khuzestan Province

Abstract: Projections of future scenarios are scarce in developing countries where human activities are increasing and impacting land uses. We present a research based on the assessment of the baseline trends of normalized difference vegetation index (NDVI), precipitation, and temperature data for the Khuzestan Province, Iran, from 1984 to 2015 compiled from ground-based and remotely sensed sources. To achieve this goal, the Sen’s slope estimator, the Mann-Kendall test, and Pearson’s correlation test were used. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 73 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Global warming and the consequent changes in climate have had a substantial impact on arid and semi-arid ecosystems, resulting in a decrease in species richness, deterioration of population structure, and alterations in the behaviour and activities of numerous other species. 34,35 Precipitation, temperature, drainage, the mineral content and the soil type, all influence the vegetation in any particular place. 36 Damaneh and team studied the ill-effects of changing climate on vegetation and concluded that periodic assessments of ecosystems are necessary and valuable for future ecosystem planning.…”
Section: Climate Change Affecting Ecosystem Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Global warming and the consequent changes in climate have had a substantial impact on arid and semi-arid ecosystems, resulting in a decrease in species richness, deterioration of population structure, and alterations in the behaviour and activities of numerous other species. 34,35 Precipitation, temperature, drainage, the mineral content and the soil type, all influence the vegetation in any particular place. 36 Damaneh and team studied the ill-effects of changing climate on vegetation and concluded that periodic assessments of ecosystems are necessary and valuable for future ecosystem planning.…”
Section: Climate Change Affecting Ecosystem Servicesmentioning
confidence: 99%
“…36 Damaneh and team studied the ill-effects of changing climate on vegetation and concluded that periodic assessments of ecosystems are necessary and valuable for future ecosystem planning. 35 Though several land cover changes, such as reforestation, agricultural intensification, urban growth, and reservoir construction, in recent times have taken place in accordance with our sustainable development objectives, the changes in land use/land cover practices adopted in earlier times have resulted in land fragmentation and land…”
Section: Climate Change Affecting Ecosystem Servicesmentioning
confidence: 99%
“…The soil water balance has been traditionally used to estimate various soil hydrological parameters (Wang and Dickinson 2012) and can be fundamental to understand the soil-plant-atmosphere relationships (Gabarrón-Galeote et al 2013) that underpin diverse hydrological issues. The spatiotemporal evolution of soil water conditions directly determines various natural Responsible Editor: Amjad Kallel conditions including the state and composition of vegetation cover, vulnerability to erosion processes, and the stability of soil aggregates (Eskandari Damaneh et al 2021). This is also fundamental to assess other phenomena including climate change and desertification, which are necessary to develop efficient water resource management plans (Jodar-Abellan et al 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…In both, we learned about ecosystem services, restoration, and alternatives to conserve bucolic landscapes and reach biodiversity territories. Moreover, interesting contributions on climate change in Mexico, Iran or Ethiopia (Eskandari Damaneh et al, 2021) were published, revealing a negative impact on vegetation, agriculture, and soils.…”
mentioning
confidence: 99%